Transformation from a traditional model to a virtual model of care in orthopaedic surgery. (June 2020) - King, D.; Emara, A. K.; Ng, M. K.; Evans, P. J.; Estes, K.; Spindler, K. P.; Mroz, T.; Patterson, B. M.; Krebs, V. E.; Pinney, S.; Piuzzi, N. S.; Schaffer, J. L.
No abstract available